Land tenure systems and property rights: Socio-legal studies in the Colombian case (2018)
This article aims to propose a methodological design to explain and assess the land titling programs that have been implemented in Colombia since 1991. The methodology incorporates elements from social and legal sciences in order to analyze the results of land titling programmes in terms of the campesinos' legal and social relationship with their land. This methodology focuses on evaluating whether land titling programs produced a change in the beneficiaries' land rights. Consequently, the proposed analysis helps to understand how legal regulations affect and transform social relationships. © 2018 The Author(s).